(untitled) (Journal of Hama University, 2025)
Endodontic surgery has become a standard of care for dental maintenance if conventional endodontic retreatment is not able to eliminate the infection, The aim of this research was to evaluate the Edema formation after Microsurgical Endodontics using piezo surgical tips and rotation burs. The sample consists of 32 teeth according to inclusion criteria from the patient that came to faculty of dentistry of Hama university. The results showed that there were no significant difference (P>0.05), after one year mentoring period between piezo surgery and rotation burs groups. After collecting the responses data were analyzed using Mann-Whitney U at the 0.05 level of significance.